Higher Mental Workload Reduces Nurses’ Compliance in Fall Injury Prevention - Hardono Hardono; Asnet Leo Bunga; Jesika Pasaribu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Nurses’ compliance with patient safety practices, particularly fall prevention, is a critical indicator of healthcare quality. Elevated mental workload may impair concentration and negatively affect nurses’ performance in implementing safety procedures. This study aimed to examine the relationship between mental workload and nurses’ compliance with fall prevention measures. A mixed-methods design with a concurrent triangulation approach was employed. Quantitative data were collected using a cross-sectional design involving 47 nurses selected through total sampling. Qualitative data were obtained through in-depth interviews with six nurses to explore their perceptions of workload and compliance. The quantitative findings revealed that Mental Demand (p = 0.001), Frustration Level (p = 0.029), and overall Mental Workload (p = 0.003) were significantly associated with nurses’ compliance in fall prevention. These results suggest that increased mental workload may affect the consistency of nurses in adhering to safety procedures. Qualitative findings indicated that nurses perceived their workload as complex, encompassing both cognitive and physical demands. High task demands, time pressure, and multiple responsibilities were identified as key challenges influencing their ability to maintain compliance.Conclusion: Nurses’ compliance is shaped by the complexity of mental workload and requires effective workload management. Organizational support, appropriate task allocation, and a supportive work environment are essential to enhance compliance and ensure patient safetyKeywords: mental workload; nurse compliance; patient safety; fall prevention